Analisis Rasio Efektifitas Terhadap APBD pada Kantor Desa Labokong Kecamatan Donri – Donri Kabupaten Soppeng 2017 – 2020 - Riski Nadia Putri; Syamsu Alam; Andi Aswan (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to test and analyze the effectiveness ratio of the APBD at the Labokong Village Office, Donri-donri District, Soppeng Regency in 2017-2020. The type of research used in this research is quantitative. The data processed is the financial report of the regional budget (APBD) from 2017 to 2020. The data analysis method used in this study is the effectiveness ratio. The results showed that in general the financial performance of the Labokong Village government, Donri-donri district, District. Soppeng is not effective yet. Keywords: financial performance; effectiveness ratio